Obama’s Health Reform: what is it, and what does it mean for the future of health care in the United States? - Greer, S. L.; Singh, S. R. (Gesundheitsökonomie & Qualitätsmanagement, 2014)
Despite high spending, the US health care system has been plagued by low quality and inadequate access to health care. In March 2010, President Obama signed into law the Patient Protection and Affordable Care Act (ACA), the most comprehensive reform of the US health care system since 1965. The focus of President Obama’s reform was to provide health insurance coverage to millions of uninsured Americans. This article first provides some background on how the United States could go without universal health insurance coverage for so long. It then presents an overview of the key components of the ACA, focusing on the individual insurance mandate and the expansion of the Medicaid health insurance program for the poor. It concludes by discussing what the ACA may mean for the future of health care in the United States. While expanded insurance coverage will improve access to health care for many of the currently uninsured, it remains to be seen in how far the ACA will also be able to improve the quality of care and bend the cost curve.
Keywords: US-amerikanische Gesundheitsreform; Patient Protection and Affordable Care Act (ACA); Krankenversicherungsschutz